Optimal Solutions of Parameters of the Modified Weibull Distribution using Least Squares and Maximum Likelihood Methods - Jamel Kenouza , Abderrahmane Belguerna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Parametric statistics are among the most important research that enables us to identify the advantages of the communities studied from the study of some of the samples taken from them. In this paper, we identify Weibwll's modified model with three parameters a. b. c, then we study the asymptotic properties of these parameters estimation, using the least squares and maximum likelihood methods by comparing estimated parameters with seized parameters by changing the size of the sample each time.